CONSUMER ACCEPTANCE TOWARD FRESHWATER MUSSEL (Pilsbryoconcha exilis) MEATBALL - Ghazali, Tengku Muhammmad; Karnila, Rahman; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pilsbryoconcha exilis is a type of freshwater mussel that commonly present in ponds in Sei Paku Village, Lipat Kain District, Riau Province. This research aims to understand the consumer acceptance on the P. exilis meatball. The meat of the mussel was used as main ingredient for the meatball. The mussel was taken from the Sei Paku area. There were 3 treatments applied, there were 150 g (K1), 200 g (K2), and 250 g (K3) mussel meat in 200 g mixed tapioca, wheat flour and egg. The meatball was flavoured with garlic, pepper and salt. Results shown that the best meatball was the K1. The organoleptic test results of this meatball (K1) was 94.6% for preference; 98.4% for texture; 90.2% for taste value, and 95% for aroma (the Duncan score were 3.49; 3.70; 3.42 and 3.41 respectively). The result of proximate analyss, however, shown that the best result was the K3, with 20.53 % protein content, 4.37% fat content, 1.29% ash content; 56.54 % water content and 17.25% carbohydrate content. In 1 gram meatball, the heavy metal (Pb and Cd) and mineral (Na, Fe, K, Ca) content were 0.0008 mg; 0.00002 mg and 0.034 mg; 0.025 mg; 0.019mg; 0.024 mg respectively.Keywords: meatball, freshwater mussel (pilsbryoconcha exilis), consumer acceptance